Non-descent vaginal hysterectomy versus total abdominal hysterectomy in fibroid uterus: a comparative study in tertiary care hospital in Uttarakhand, India - Goswami, Divya; Ramola, Monika; Gupta, Vineeta; Kumari, Nidhi; Kumari, Rashmi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Hysterectomy comprises one of the most common elective surgeries in hysterectomy as the operative modality. The vaginal route of hysterectomy has been largely reserved for prolapsed uteri or non-descent cases with nearly normal size uteri. In the state of Uttarakhand, where specialized health services are difficult to access, abdominal route forms the prime choice for surgical treatment of fibroid uterus. A multitude of research data has suggested the superiority of vaginal over abdominal route. Despite this, there is a definite hesitation amongst gynecologists to resort to NDVH for fibroid uterus. This study was done with the objective to compare and analyze the outcome of abdominal vs. vaginal route for uterine fibroids. Methods: A retrospective study carried out for 80 patients admitted in one year duration with the diagnosis of fibroid uterus. These patients underwent either total abdominal hysterectomy (TAH) or (non-descent vaginal hysterectomy) NDVH depending upon patient discretion after thorough discussion with the operating doctor. Results: The results displayed vaginal route to be superior in terms of operative time, intra-operative blood loss and postoperative recovery. Conclusions: We concluded from this study that patients can be safely offered NDVH, thus minimizing the need for laparotomy for fibroid uterus.